'Safe Space' for Jewish and Arab Teachers Dealing with Controversial Issues. Issue 2 (3rd April 2023) - Paul-Binyamin, Ilana; Hayosh, Tali
ABSTRACT: This research examines perceptions of 51 teachers in Israeli society, about the national educational theme project "Maintaining unitedness, maintaining uniqueness." This topic is highly controversial in the divided Israeli society. This research mainly conceptualizes the ways in which teachers negotiate the governmental mission while creating their own "safe space, " in which they can operate safely: (1) a conversion of the socio-political discourse into a person-oriented discourse; (2) embodiment of an intra-national particularity approach; and (3) elaboration of significant consensual aspects of the society. This research stimulates a reexamination of teachers' pedagogical leadership and it also comprises recommendations for policymakers.